Modernist Idealism Ambivalent Legacies of German Philosophy in Italian Literature - Subialka, Michael J. (University of Toronto Press, 2022)
Offering a new approach to the intersection of literature and philosophy, Modernist Idealism contends that certain models of idealist thought require artistic form for their full development and that modernism realizes philosophical idealism in aesthetic form. This comparative view of modernism employs tools from intellectual history, literary analysis, and philosophical critique, focusing on the Italian reception of German idealist thought from the mid-1800s to the Second World War. Modernist Idealism intervenes in ongoing debates about the nineteenth- and twentieth-century resurgence of materialism and spiritualism, as well as the relation of decadent, avant-garde, and modernist production. Michael J. Subialka aims to open new discursive space for the philosophical study of modernist literary and visual culture, considering not only philosophical and literary texts but also early cinema. The author's main contention is that, in various media and with sometimes radically different political and cultural aims, a host of modernist artists and thinkers can be seen as sharing in a project to realize idealist philosophical worldviews in aesthetic form.